The role of nurses in hemotherapy safety: challenges and perspectives (Research, Society and Development, 2022)
The Hemotherapy service is considered of paramount importance for the maintenance of the life of patients with certain pathologies that require procedures aimed at hemotherapy. This study aims to analyze the role of nurses during work processes, highlighting transfusion safety and emphasizing the instruments and materials used in order to ensure the safety and quality of the blood product transfusion procedure. The methodological approach was understood as a descriptive-exploratory literature review based on searches in the electronic databases Google Scholar, Scientific Electronic Library Online – SCIELO and PUBMED during the months of August 2019 to June 2020. 159 were found. articles, after applying the inclusion and exclusion criteria, a final sample of 09 articles was constituted. In this way, the importance of the nurse professional in the blood transfusion process is highlighted, as well as the direction to guarantee safety during the performance of the procedure mediated by the breadth of the development of their activities as well as the possibility of strengthening health practices by through continuing education, the team in the blood products sector.